Association of distinct α2 adrenoceptor and serotonin transporter polymorphisms with constipation and somatic symptoms in functional gastrointestinal disorders. Issue 6 (11th May 2004) - Kim, H J; Camilleri, M; Carlson, P J; Cremonini, F; Ferber, I; Stephens, D; McKinzie, S; Zinsmeister, A R; Urrutia, R
Abstract : Background: The role of genetics in the phenotypic manifestations of irritable bowel syndrome (IBS) is unclear. Our aims were: (1) to compare the prevalence of polymorphisms of alpha 2 (α2 ) adrenoceptors, norepinephrine transporter, and serotonin transporter protein (soluble carrier protein member 4 (SLC6A4)) promoter in patients with lower functional gastrointestinal disorders (FGID) and in healthy controls; and (2) to test associations of these genetic variations with symptoms of IBS and high somatic symptom scores. Methods: Validated bowel and somatic symptom questionnaires characterised the phenotype: 90 with IBS constipation (IBS-C), 128 IBS diarrhoea, 38 IBS alternating bowel function, and 20 chronic abdominal pain. Logistic regression analyses assessed associations of different polymorphisms for α2 adrenoceptor and SLC6A4 with IBS or chronic abdominal pain phenotypes and high somatic score. Results: Two distinct polymorphisms independently appeared to be associated with the phenotype IBS-C: α2C Del 322–325 (odds ratio (OR) 2.48 (95% confidence interval (CI) 0.98, 6.28); p = 0.05) and α2A −1291 (C→G) (OR 1.66 (95% CI 0.94, 2.92); p = 0.08) relative to wild-type. Overall, the α2C Del 322–325 polymorphism (alone or combined with other polymorphisms) was also significantly associated with a high somatic symptom score (OR 2.2 (95% CI 1.06, 4.64); p = 0.03). Combinations of polymorphisms were also associated with high somatic scores. Conclusion: Functionally distinct α2A and α2C adrenoceptor and serotonin transporter polymorphisms are associated with constipation and high somatic symptoms in patients with lower functional gastrointestinal disorders, although the strength of the genetic contribution to the phenotype is unclear.